Perfil de sensibilidade de cepas de Coccidioides posadasii a associação de drogas antimicrobianas - Medrano, Délia Jéssica Astete (2010)
The coccidiodomicose is a systemic infection, predominantly lung caused by dimorphic fungi Coccidioides immitis and C. posadasii. Brazil is among the countries with endemic areas of coccidiodomicose, confined to the semiarid areas of Northeast Brazil. This scenario leads to a larger investigation into new strategies for an injunction against C.posadasii. Based on this context, the purpose of this study was to investigate new strategies, to evaluate the in vitro interaction of the major antifungal agents used in the treatment of coccidioidomycosis, analyze the inhibitory effect in vitro antimicrobial drugs, such as sulfamethoxazole and trimethoprim (SMX / TMP ) associated or not with amphotericin B (AMB) and evaluate the in vitro interaction of antituberculosis drugs with antifungal drugs against C. posadasii strains isolated in northeastern Brazil. The study was conducted in test macrodilution according to the protocol described in document M-38A, standardized by the Clinical Laboratory Standars Institute (CLSI, 2002). The synergistic interaction of the drugs was evaluated by the Checkerboard method. This study showed that the eight combinations of two antifungal drugs such as amphotericin B with azole derivatives and voriconazole with derivative azole and caspofungin, respectively showed inhibitory effect in vitro against the isolates of C. posadasii, but only a combination of voriconazole with amphotericin B showed synergistic interaction, whose minimum inhibitory concentration (MIC) was reduced by 15 times when compared with the MIC of the drug tested alone. SMX/TMP had an inhibitory effect in vitro against strains of C. posadasii, however, decreased the MIC of AMB at 5,85 times when associated with SMX / TMP. Regarding the 24 combinations of antifungal drugs with antituberculosis drugs tested showed any inhibitory effect in vitro against the isolates of C. posadasii. Of the 24 combinations, synergistic interactions were observed in 16 associations, of which, amphotericin B with rifampicin, itraconazole or rifampicin with ethambutol or pyrazinamide, ethambutol with fluconazole and voriconazole with ethambutol MICs were reduced ten-fold when compared with the MICs of drugs tested in isolation. Future studies in animal models are needed to confirm the usefulness of these combinations. This work is a source of support for new investigations of combinations that result in synergistic interactions, as well as to determine the correlation of results in vivo.